DEVELOPMENT OF THE MAGIC TOUCH POCKETBOOK AS A MEDIUM FOR SELF-POTENTIAL INFORMATION SERVICES IN SPECIALIZATION SELECTION - Hayat, Muhammad Yusran; Sinring, Abdullah; Latif, Suciani (JURNAL NALAR PENDIDIKAN, 2025)
This study aims to develop a pocketbook as an information service medium to help students recognize and explore their potential before selecting a specialization class. Choosing an appropriate specialization is expected to optimize students' skill development. This study employs the ADDIE development model by Lee & Owens (2004), which consists of five stages: (1) Analysis (Need Assessment & Front-End Analysis), (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The research subjects consist of 34 seventh-grade students at MTsN 1 Kota Makassar, involving counseling teachers and lecturers as material and media validators. Data were collected through questionnaires and interviews and then analyzed using descriptive qualitative and quantitative methods. The developed product is a pocketbook called Magic Touch. The research findings indicate that Magic Touch is feasible as an information service medium for recognizing and exploring students' potential. This is supported by validation results from material and media experts, as well as positive feedback from the research subjects. This pocketbook is expected to serve as an effective tool for students in determining a specialization that aligns with their potential, thereby supporting both their academic and non-academic development.